Activation of the SOS response increases the frequency of small colony variants. (December 2015) - Vestergaard, Martin; Paulander, Wilhelm; Ingmer, Hanne
Abstract Background InStaphylococcus aureus sub-populations of slow-growing cells forming small colony variants (SCVs) are associated with persistent and recurrent infections that are difficult to eradicate with antibiotic therapies. In SCVs that are resistant towards aminoglycosides, mutations have been identified in genes encoding components of the respiratory chain. Given the high frequencies of SCVs isolated clinically it is vital to understand the conditions that promote or select for SCVs. Results In this study we have examined how exposure to sub-inhibitory concentrations of antibiotics with different mechanism of action influence the formation of SCVs that are resistant to otherwise lethal concentrations of the aminoglycoside, gentamicin. We found that exposure ofS. aureus to fluoroquinolones and mitomycin C increased the frequency of gentamicin resistant SCVs, while other antibiotic classes failed to do so. The higher proportion of SCVs in cultures exposed to fluoroquinolones and mitomycin C compared to un-exposed cultures correlate with an increased mutation rate monitored by rifampicin resistance and followed induction of the SOS DNA damage response. Conclusion Our observations suggest that environmental stimuli, including antimicrobials that reduce replication fidelity, increase the formation of SCVs through activation of the SOS response and thereby potentially promote persistent infections that are difficult to treat.